Analysis of sustainable tourism and the development of the destination's biodiversity potential - Žugaj, Brankica; Kalambura, Sanja (Crisis Management Days, 2024)
Sustainability and the tourism sector are key elements of modern society that require increasing attention in the context of biodiversity. Tourism, as one of the fastest growing sectors of the global economy, plays an important role in the conservation and promotion of biodiversity, but at the same time can have negative impacts on natural ecosystems. The key element of sustainable and environmentally friendly tourism is the preservation of natural ecosystems. The diversity of flora and fauna will therefore attract tourists and form the basis for the development of diverse tourism products and experiences. Sustainability in tourism implies a balance between economic, socio-cultural and environmental aspects, while the promotion of sustainable tourism implies a management of tourism activities that minimises the negative impact on the environment, promotes the protection of natural and cultural assets and supports local development and economic prosperity. Through the prism of biodiversity, sustainable tourism is based on the respect of natural processes and the protection of ecosystems, which includes the promotion of ecotourism, the conservation of natural habitats and the protection of endangered species, as well as educational activities and the sensitisation of visitors to the importance of biodiversity. However, achieving sustainability in the tourism sector through the prism of biodiversity faces challenges such as excessive infrastructure construction, over-exploitation of resources, mass tourism and irresponsible visitor behaviour. Therefore, it is important to implement strict destination management policies, regulate tourism activities, promote environmentally conscious travelling, and encourage cooperation between tourism and environmental protection stakeholders. Overall, the sustainability of tourism through the prism of biodiversity requires an integrated approach that involves co-operation between the tourism sector, local communities, conservationists, authorities, and other stakeholders to ensure that tourism contributes to the conservation and promotion of biodiversity richness while providing economic benefits and improving the quality of life of local communities. This paper examines the interaction between sustainability, tourism, and biodiversity, focusing on the importance of natural resource conservation for the long-term sustainability of the tourism sector.